Formulation and Evaluation of Lacquer of fluconazole for Transungual Drug Delivery System - Verma, Vishal; Bisht, Manoj; Bhardwaj, Manoj (Journal of Neonatal Surgery, 2025)
Transungal drug delivery system refers to the delivery of drugs through the nail plate (the hard, visible part of the nail) for therapeutic purposes. The study was based on the Formulation and Evaluation of Lacquer of fluconazole for Transungual Drug Delivery System. The fluconazole was purchased from the Dhamtec Pharma and Consultants, Navi Mumbai, India. The nail lacquer using fluconazole was formulated by simple mixing method. Characterization of nail lacquer was done through various parameters i.e., non-volatile content, drying time, smoothness, gloss, water resistance, viscosity, color, in-vitro transungual permeation studies and stability studies. Evaluation of antifungal activity of nail lacquers using disc diffusion method. In results, the color was found as transparent and homogenous in F1-F4 Nail Lacquers of fluconazole. It exhibited a maximum in-vitro transungual permeation in F3 as 95.7±0.6 %. The stability test was carried out for 1 month and there was no significant change observed in colour, non-volatile content, drying time, smoothness and water resistance. All the formulations of fluconazole lacquer exhibited significant anti-fungal activity. Zone inhibition was estimated as 11.2 mm, 13.8 mm, 19.4mm, 16.1 mm and 32.4 mm in F1, F2, F3, F4 and Fluconazole group. In conclusion, fluconazole lacquer (F1-F4) demonstrated a potential characterization parameter when estimated for color, non-volatile content, drying time, smoothness, water resistance and in-vitro transungual permeation studies. However, F3 exhibited a much significant data. The anti-fungal potential was also estimated highest in F3. Thus, it can be said that F3 is the optimized formulations.